Evaluation of Crude Oil Extracts from Plants for Controlling Maize Infestations Caused by the Weevil Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) - Fikadu Kifle; Melaku Girma; Araya Gebresilassie; Yitbarek Woldehawariat; Estifanos Ele (Psyche: A Journal of Entomology)
Plant extracts have emerged as promising options for the controlling maize weevil due to their bio-insecticidal potential and reduced environmental impact in developing countries. The experiments were carried out to assess the effectiveness of crude plant oil from Eucalyptus globulus, neem (Azadirachta indica), marigold (Tagetes minuta), moringa (Moringa stenopetala), Ayobangira (Ocimum basilicum), custard apple (Annona squamosa), and Chenopodium ambrosioides. These extracts were evaluated at concentrations of 0.05, 0.1, and 0.15 g per gram, diluted with 10 ml of deionized water, and applied to 50 grams of maize against Sitophilus zeamais. The insects were reared in a plastic jar with one liter of capacity. For comparison, Actellic 2% dust at a dose of 0.05 g/50 gram maize was utilized as a standard check, with untreated seeds serving as the control. The experiment followed a completely randomized design with triple replications. Adult S. zeamais mortality was approximately 83% for maize seeds treated with A. indica, T. minuta, A. squamosa, and E. globulus within 96 hours of treatment at a rate of 0.10 g and 0.15 g/50 g of maize. Plant crude oil treatments with A. indica and E. globulus at all tested rates at higher concentrations (0.10 g and 0.15 g per 50 g) inhibited S. zeamais F1 progeny production with approximately 97.2 ± 0.03%. The proportion of maize grain infection by S. zeamais was dramatically reduced after treating the plant with crude oil. Furthermore, the oil treatment for these plants had no effect on seed germination percentage. Overall, the findings suggest that these plant crude oil extracts can be utilized to control S. zeamais.